The Use of Robomind Application in Problem Based Learning Model to Enhance the Student’s Understanding on the Conceptual Programming Algorithm. - Anggun Nofitasari; Rosihan Ari Yuana; Dwi Maryono (Universitas Sebelas Maret, 2017)
The purpose of this research was to improve understanding of basic programming algorithms concept of class X TKJ 1 SMK N 1 Banyudono on Basic Programming lesson using robomind application through Problem Based Learning model. This research was a Classroom Action Research, with research subjects were 33 students of class X TKJ 1 SMK N 1 Banyudono. This research was started by identifying the problems occured in the classroom. Then, we designed actions to solve the problem in a cycle of actions. In this research, the actions were done in two cycles. Each cycle consists of planning, implementation, observation and reflection. Data was collected by observation of the learning activities in the classroom and comprehension tests after each cycle. Analysis of the data was performed using quantitative and qualitative analysis interactive technique. The results showed that the implementation of the Problem Based Learning model using media assistance robomind applications could enhance students' understanding of the program algorithm. It is shown by the completeness of comprehension tests on pre-cycle 37.5%, 44.8% in the first cycle, and 93.3% in the second cycle. This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.